2010
DOI: 10.1111/j.1465-7295.2008.00172.x
|View full text |Cite
|
Sign up to set email alerts
|

The Knowledge Production Function for University Patenting

Abstract: "We estimate a knowledge production function for university patenting using an individual effects negative binomial model. We control for Research and Development expenditures, research field, and the presence of a Technology Transfer Office. We distinguish between three kinds of researchers: faculty, postdoctoral scholars (postdocs), and PhD students. For the latter two, we also distinguish by visa status. We find patent counts to relate positively and significantly to the number of PhD students and number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 23 publications
4
35
0
3
Order By: Relevance
“…We argue that this excellent performance of the Chinese with respect to other students is most likely explained by selection processes. Our findings strengthen and complement other studies that have found that migrant scientists and engineers make disproportionate contributions to U.S. innovation (Levin & Stephan 1999;Hunt 2011, Stuen, Mobarak & Maskus 2011Chellaraj, Maskus & Mattoo 2008, Gurmu, Black & Stephan 2010. The influx of talented students is an important benefit to host universities.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We argue that this excellent performance of the Chinese with respect to other students is most likely explained by selection processes. Our findings strengthen and complement other studies that have found that migrant scientists and engineers make disproportionate contributions to U.S. innovation (Levin & Stephan 1999;Hunt 2011, Stuen, Mobarak & Maskus 2011Chellaraj, Maskus & Mattoo 2008, Gurmu, Black & Stephan 2010. The influx of talented students is an important benefit to host universities.…”
Section: Discussionsupporting
confidence: 89%
“…This paper contributes to the growing literature on immigration and innovation. Previous studies have typically analyzed the relationship between the innovative performance of cities (Kerr & Lincoln 2010), states (Hunt & Gauthier-Loiselle 2010), firms (Kerr & Lincoln 2010;Passerman 2011) or universities (Stuen, Mobarak & Maskus 2011;Chellaraj, Maskus & Mattoo 2008;Gurmu, Black & Stephan 2010) and the share of migrants in these entities.…”
mentioning
confidence: 99%
“…Several authors have used this empirical tool to analyse the production of university patents at various levels (e.g. Coupé 2003;Foltz et al 2000Foltz et al , 2003Payne and Siow 2003;Azagra-Caro et al 2006a, b;Baldini et al 2006;Acosta et al 2009;Gurmu et al 2010). Our framework is marked by two differences.…”
Section: Econometric Modelmentioning
confidence: 99%
“…In contrast, Payne and Siow (2003), Adams (2009), and Gurmu, Black, and Stephan (2010) find positive effects of research grants on knowledge production in universities.…”
mentioning
confidence: 89%